Enhancement of Cloud Data Protection using Attribute Based Encryption with Multiple Keys: A Survey - K. Usha Rani, Md. Sameera (Mathematical Statistician and Engineering Applications, 2023)
Cloud Computing is an information technology innovation that enables clients to access system resources, computing power and storage on demand without the need for their direct supervision. It involves sending user data and application software to a remote data repository or cloud that users cannot directly control. As a result, users of cloud computing technology are mainly concerned with ensuring the protection and confidentiality of their information. Despite the growing popularity of cloud technology, there are still concerns about data security, privacy, reliability and interoperability that must be addressed. This article presents a survey conducted on the effectiveness of using Multiple Keys for a single file and the role of Attribute Based Encryption (ABE) with Multiple Keys, also known as Multi Authority Attribute Based Encryption (MA-ABE), in improving data security in the cloud. The survey examines how these techniques can be applied to increase the security of cloud based data, particularly in industries such as healthcare, finance, and government agencies that handle highly sensitive data and require strict access control.